2015
DOI: 10.1177/1071100715570895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fragment Size and Postoperative Joint Congruency on Long-Term Outcome of Posterior Malleolar Fractures

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 24 publications
(32 reference statements)
7
116
0
9
Order By: Relevance
“…The ankle range of motion (ROM) was measured, and the difference of the dorsiflexion between the injured and uninjured side was calculated and presented as dorsiflexion restriction [19, 20]. Visual Analog Scale (VAS) was used to evaluate local pain.…”
Section: Methodsmentioning
confidence: 99%
“…The ankle range of motion (ROM) was measured, and the difference of the dorsiflexion between the injured and uninjured side was calculated and presented as dorsiflexion restriction [19, 20]. Visual Analog Scale (VAS) was used to evaluate local pain.…”
Section: Methodsmentioning
confidence: 99%
“…Disappointingly, this still included over 40% of the patients in whom the posterior malleolus had been fixed. 56 The authors of a CT-based study dismissed earlier papers that are based on plain radiographs. However, their own retrospective series had CT data for only 57% of the 42 patients.…”
Section: Cite This Articlementioning
confidence: 99%
“…Therefore, the authors suggested that anatomic reduction and internal fixation should be used when the posterior malleolus fracture fragment size is >25% of the articular surface. In a previous study, Drijfhout van Hooff et al divided 131 patients into three groups depending on the fragment size: <5%, 5%-25%, or >25% 21 . The average follow-up period was 6.9 years (range, 2.5-15.9).…”
Section: Management Of Posterior Malleolus Fracturesmentioning
confidence: 99%